Analysis of The Effectiveness and Efficiency of Expenditure Budget Implementation in Balikpapan City - Rifda Khaerani, Thalita; Susilowati, Tri; Dea Syafira, Anisa (Riviera Publishing, 2023)
The budget can be used as a guideline in carrying out its duties. Public sector organizations are required to consider value for money in making policies and carrying out their activities. The purpose of this study is to determine the level of effectiveness and efficiency of the implementation of the Balikpapan City regional budget for 2019-2022. The method used in this study is quantitative descriptive analysis with data analysis using effectiveness and efficiency measurement methods. The results of this study show that the level of effectiveness and efficiency of budget implementation in Balikpapan City in 2019-2022 has fluctuated. The implementation of the Balikpapan City regional budget in 2019-2022 as a whole meets the criteria of being quite effective. The lowest percentage of efficiency in 2019 was 95.01%, which falls under the category of less efficient. The highest efficiency rate was in 2020, with a percentage of 86.96%, with the criteria of being quite efficient. This study implies that fluctuations in the level of effectiveness and efficiency of Balikpapan City's APBD implementation may indicate factors that change from year to year. It is necessary to conduct in-depth analysis to identify the causes of such fluctuations in order to take appropriate corrective measures. Although there are fluctuations, the overall implementation of the Balikpapan City APBD is considered quite effective. This could be an indication that there are certain aspects that are managed well, but it is still necessary to focus on elements that may cause fluctuations.